Przyczynek do badań nad czasopiśmiennictwem romskim w Polsce - Kuć , Bogusława (Acta Universitatis Lodziensis. Folia Librorum, 2009)
The article outlines the issue of Romani periodical press in Poland, as a new phenomenon on Polish press market. It also briefly discusses the origin, development as well as various aims and functions of such periodicals as: „Rrom p-o drom”, „Dialog=pheniben”, „Romano Atmo” and „Studia Romologica”. In addition, the article drops a hint about the existence and the role of the following ephemerides: “Taboreska”, “Romani Dźipen” and “Usłyszcie nas”.